ANALISIS PELUANG AI DALAM MENDUKUNG PEMBELAJARAN BERDIFERENSIASI DI SD NEGERI 02 SIMPANG TIGA CUBADAK - Faisa, Zayyan; Nanda Fatimah, Sri; Tokhoriah, Afifah; Adrias Adrias; Chandra Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This scientific paper, entitled "Analysis of AI Opportunities in Differentiated Learning at SD N 02 Cubadak," aims to examine the potential use of artificial intelligence (AI) to support differentiated learning in elementary schools. Differentiated learning is a strategy teachers can employ to meet the needs of each student, each with their own unique characteristics. Differentiation is a process within teaching and learning activities that prioritizes students based on their abilities, preferences, and individual needs during the learning process (Di & Dasar, 2022). This research employed qualitative descriptive methods through online interviews with teachers at SD Negeri 02 Simpang Tiga Cubadak, conducted through reviewing various scientific journals and relevant sources. The interviews indicated that AI has the potential to support personalized learning, assist in the development of materials tailored to students' abilities, provide faster assessment and feedback, and enhance teacher creativity in designing learning.